Industrial Ornament, Modern Symbol: New Orleans’ First Waterworks on the Mississippi River - Rina Faletti (Open Rivers, 2017)

(untitled)
The second city in U.S. history to debut a modern industrial urban waterworks system was New Orleans Designed and built between 1811 and 1820, the New Orleans Waterworks displayed the most advanced innovations of its day, both in hydraulic engineering technology and in aesthetic architectural design...